2015
DOI: 10.1590/2175-7860201566413
|View full text |Cite
|
Sign up to set email alerts
|

The naturalized flora of Brazil: a step towards identifying future invasive non-native species

Abstract: Human-mediated species introductions are one of the defining factors of the Anthropocene. Non-native species can form invasive populations that affect biodiversity, ecosystem services, or farming. Here I summarized data on naturalized vascular species from the Brazilian list of seed plants and tested the hypotheses that more populated regions and biomes with less remaining natural vegetation harbor more naturalized species. The Atlantic Forest had the largest number of naturalized species, whereas the Pampa ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 15 publications
0
10
0
9
Order By: Relevance
“…2009) and was subsequently invaded by four non‐native African perennial grasses: Melinis minutiflora , Urochloa decumbens , Andropogon guayanus and Hyparrhenia rufa . All these non‐native species have been present in the region for some time and are now considered invasive (Zenni, ; Zenni & Ziller, ). Immediately prior to the experiment we surveyed the area and found that M. minutiflora and U. decumbens were dominant in the area of the experiment (widespread throughout the experimental area with more than 50% plant cover each species), whereas A. guayanus and H. rufa had only a scattered presence (<5% plant cover).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2009) and was subsequently invaded by four non‐native African perennial grasses: Melinis minutiflora , Urochloa decumbens , Andropogon guayanus and Hyparrhenia rufa . All these non‐native species have been present in the region for some time and are now considered invasive (Zenni, ; Zenni & Ziller, ). Immediately prior to the experiment we surveyed the area and found that M. minutiflora and U. decumbens were dominant in the area of the experiment (widespread throughout the experimental area with more than 50% plant cover each species), whereas A. guayanus and H. rufa had only a scattered presence (<5% plant cover).…”
Section: Methodsmentioning
confidence: 99%
“…The Cerrado is a biodiversity hotspot facing rapid transformations due to deforestation, land conversion and habitat fragmentation (Strassburg et al, ). The Cerrado is also a hotspot of naturalized and invasive species, with more than 200 known widespread naturalized plant species across the biome (Dawson et al, ; Zenni, ; Zenni & Ziller, ). Previous research has documented severe impacts of plant invasions, mainly African grasses, in different Cerrado formations (from grassland, savanna to forest formations).…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, useful information is lost when naturalized and invasive species are excluded from published plant lists (Moro et al 2012). Reviewing the Brazilian flora (BFG 2015), Zenni (2015) diagnosed the presence of nonnative species in all biomes, but especially the Atlantic Forest where the largest number of naturalized species was found. Human actions and activities were directly correlated with the observed patterns of naturalization (Zenni 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Um dos principais indicadores da ação humana sobre ecossistemas é a presença de espécies exóticas invasoras em áreas naturais (ZENNI, 2015;ZENNI et al, 2016). São consideradas exóticas as espécies transportadas de uma dada região geográica para outra em que não ocorreriam naturalmente, independentemente de seu eventual impacto sobre os ecossistemas naturais, sendo o transporte realizado por ação humana intencional ou acidental (LOCKWOOD et al, 2007).…”
Section: Introductionunclassified
“…De fato, conforme demonstrado por Zenni (2015), regiões mais populosas e com menor área natural remanescente tendem a apresentar maior número de espécies invasoras, como é o caso da Floresta Atlântica. No entanto, a despeito do grau de conservação da vegetação e das fortes pressões antrópicas, os remanescentes lorestais exercem papel importante na conservação da biodiversidade da região metropolitana de São Paulo, visto que ainda resguardam rica fonte de propágulos (DAVIES; SHELEY, 2011).…”
Section: Introductionunclassified